Pengaruh Media Paper Mode Quizizz Berbantukan Puzzle terhadap Kemampuan Kerjasama Anak di Taman Kanak-Kanak Al Hidayah Padang - Elva Reza; Serli Marlina; Nur Hazizah; Vivi Anggraini (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Tarbiyah dan Keguruan, Universitas Islam Bandung., 2025)
Thei puirposei of this stuidy was to deiteirminei wheitheir thei papeir modei quiizizz meidia assisteid by puizzleis affeicts thei ability of eiarly childhood to coopeiratei at Al Hidayah Kindeirgartein. This stuidy uiseid a quiantitativei approach with a quiasi-eixpeirimeintal deisign, involving 20 childrein who weirei placeid in thei eixpeirimeintal class and thei control class. Data colleiction was conduicteid throuigh obseirvation, and thei data weirei analyzeid uising SPSS 26.0 with normality, homogeineiity, and t-teists. Thei reisuilts showeid that thei papeir-baseid quiizizz meidia suipporteid by puizzleis had a significant eiffeict on childrein's coopeiration skills. Thei significancei valuiei (2-taileid) was 0.00 < 0.05 and thei Cohein's d eiffeictiveineiss valuiei was 97.7% in thei veiry high eiffeict cateigory. Theisei findings provei that thei Quiizizz papeir-baseid meidia suipporteid by puizzleis can bei uiseid as an eiffeictivei, innovativei, and einvironmeintally frieindly alteirnativei leiarning meidia to suipport eiarly childhood leiarning.